2020
DOI: 10.1108/hff-02-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

MHD hybrid nanofluid flow over a permeable stretching/shrinking sheet with thermal radiation effect

Abstract: Purpose This study aims to investigate the heat transfer characteristic of the magnetohydrodynamic (MHD) hybrid nanofluid over the linear stretching and shrinking surface in the presence of suction and thermal radiation effects. Design/methodology/approach Mathematical equations are transformed into pairs of self-similarity equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Further, Ellahi et al (2020b), Ahmed et al (2019) and Zeeshan et al (2019) carried out numerical studies on fluid flow with nanoparticle mixtures. The additional references in the study of hybrid nanofluid are listed from the literature, such as Manjunatha et al (2019), Waini et al (2019c), Devi and Devi (2016a) and most recently by Yashkun et al (2020b).…”
mentioning
confidence: 99%
“…Further, Ellahi et al (2020b), Ahmed et al (2019) and Zeeshan et al (2019) carried out numerical studies on fluid flow with nanoparticle mixtures. The additional references in the study of hybrid nanofluid are listed from the literature, such as Manjunatha et al (2019), Waini et al (2019c), Devi and Devi (2016a) and most recently by Yashkun et al (2020b).…”
mentioning
confidence: 99%
“…Waini et al [16] also reported that the presence of a huge volume fraction of copper intensifies the skin friction coefficient and the local Nusselt number. Many other recent interesting investigations towards hybrid nanofluid, focusing on alumina and copper as the hybrid nanoparticles, with various configurations of parameters, have also been revealed by Yashkun et al [17], Lund et al [18,19], Aladdin et al [20], Roşca et al [21], Khashi'ie et al [22][23][24][25], Roy and Pop [26], Zainal et al [27], Anuar et al [28], Gangadhar et al [29] and Wahid et al [30].…”
Section: Introductionmentioning
confidence: 87%
“…Slip and thermal radiation effects on the MHD Casson effect were investigated by Raza [2] with concluding remarks that the concentration boundary layer thickness is hiked as the chemical reaction parameter gets higher. Yashkun et al [3] highlighted the MHD hybrid radiative nanofluid past a shrinking/stretching surface. One of the conclusions was that suction parameter enhances the shrinking/stretching parameter range for which the solution exists.…”
Section: Introductionmentioning
confidence: 99%